Health workers knowledge, attitudes and practices towards youth-friendly sexual and reproductive health service delivery in Calabar Metropolis, South-South, Nigeria - Felicity Nneoma Ike; Elvis Anyaehiechukwu Okolie; Phillip Etabee Bassey (BioSocial Health Journal)
Introduction: The provision of youth-friendly sexual and reproductive health services (YFSRHS) is critical to improving young people’s health outcomes. However, millions of young people in Nigeria face numerous barriers to accessing YFSRHS. Therefore, this study assessed the health workers’ knowledge, attitude, and practices towards the delivery of YFSRHS in Calabar Metropolis. Methods: A quantitative cross-sectional descriptive design was utilised for this study. A stratified random sampling technique was employed to select 424 health workers from 50 primary healthcare facilities in Calabar Metropolis. Data was collected using a 30-item structured questionnaire and analysed using SPSS version 26. Results: The majority (72.8%) of the health workers were females, with 44.7% aged between 21 and 30. A considerable proportion of the respondents had moderate (56.3%) to high (29.9%) knowledge of YFSRHS. Despite most respondents having positive attitudes, a high proportion recorded poor practices, as 58.3% provided sexual and reproductive health services without the use of written guidelines, 87.4% were not trained, and a further 52.9% reported that they did not provide these services in a safe space. Lack of motivation, religious and cultural beliefs, and lack of training were identified as barriers to the delivery of YFSRHS. Conclusion: Moderate to high levels of knowledge and positive attitudes among health workers did not translate into desired practices in YFSRH service delivery. A re-orientation of healthcare workers within Calabar Metropolis is needed to improve the delivery of YFSRHS for the prevention of sexually transmitted infections (STIs), teenage pregnancy and maternal deaths among young people.